Comparative education histories: a postscript. Issue 1 (2nd January 2018) - Manzon, Maria
ABSTRACT: Comparative education is two centuries old. Many mainstream historical narratives claim that the field began with the iconic opus of Marc-Antoine Jullien de Paris (1817). This article offers to re-theorise the histories of comparative education. It suggests casting a far-sighted and panoramic look at the field's origins. An underlying assumption in these histories is the embeddedness of comparative education in ever-changing world orders. The article concludes with a puzzle for future work on a global history of comparative education.